A global history of the ancient world Asia, Europe, and Africa before Islam - Seland, Eivind Heldaas (Routledge, an imprint of the Taylor & Francis Group, 2022)
"Ancient history has traditionally focused on Greece and Rome. This book takes a global approach to the distant past, following the development of human societies across the globe from the last Ice Age, 11,700 years ago, to the rise of Islam in the seventh century CE. The only book of its kind, A Global History of the Ancient World provides succinct narratives of the first Asian, African, and European civilizations and their importance for later history without foregoing the key topics of conventional textbooks. Thematic overviews give truly global perspectives on connections, disconnections and parallel developments shaping the ancient world. Written for students of history, classics, and related disciplines, the book will appeal to anyone interested in widening their view of early history"--Provided by publisher.